Assessing the Test-Retest Reliability of MyotonPRO for Measuring Achilles Tendon Stiffness - Krystof Volesky; Jan Novak; Michael Janek; Jakub Katolicky; James J. Tufano; Michal Steffl; Javier Courel-Ibáñez; Tomas Vetrovsky (Journal of Functional Morphology and Kinesiology)
Objectives: This study evaluates the test-retest reliability and inter-rater reliability of the MyotonPRO for measuring Achilles tendon stiffness at two standardized sites over various time frames and settings. Methods: Eight healthy participants underwent assessments by three raters over six visits. Tendon stiffness was measured at proximal (mid-portion) and distal (insertional) regions of the Achilles tendon at various time frames (10–15 s, 10–15 min, 24 h, and 14 days apart). Measurements included participant repositioning and two activity stimuli (daily living and sport). Reliability was calculated using the intraclass correlation coefficient (ICC), its 95% confidence interval, coefficient of variation, standard error of measurement, and minimal detectable change. Results: Short-term reliability (10–15 min) was excellent, with an ICC of 0.956 (0.929–0.974). Between days reliability (24 h) was good, with an ICC of 0.889 (0.802–0.938). Between weeks reliability (2 weeks) was good with an ICC of 0.886 (0.811–0.931). Short-term reliability with the simulation of activity of daily living was good, with an ICC of 0.917 (0.875–0.945). Short-term reliability with the simulation of sport was good with an ICC of 0.933 (0.891–0.96). Between days reliability with the simulation of sport was good, with an ICC of 0.920 (0.859–0.955). Conclusions: When used in a standardized position, the MyotonPRO demonstrates reliable repeated measurements of Achilles tendon stiffness. This protocol provides a foundation for clinical research and rehabilitation by clarifying expected reliability across minutes, days, and weeks, thus aiding clinicians and researchers in monitoring tendon adaptations and making evidence-based decisions.